Relação entre autoimagem genital e atividade sexual em mulheres idosas - Silva, Janine Barbosa da (2022)
Aging is characterized as a progressive process that subjects individuals to physical and functional changes. Genital self-image is conceptualized as a feeling or behavior that arises from direct or indirect experiences involving the genitals. A woman's perception of her genital organ can be influenced by sexual experiences. The aim of the study was to investigate the relationship between genital self-image and sexual activity in elderly women. A retrospective research was carried out from a database of an observational research carried out with elderly women aged 60 to 80 years old in the city of Santa Maria, Rio Grande do Sul. Information from the database of sexually active, with preserved cognitive function was included. Elderly women whose records were incomplete in the database, women who reported difficulty in responding to the research instruments, as well as those with active self-reported genital pathology were excluded. Data collection was performed using the following instruments: Adapted Assessment Form used by the Gerontology Laboratory (LAGER) of the Universidade do Estado de Santa Catarina - UDESC, Female Genital Self-Image Scale (FGSIS), Female Sexual Function Index/Index of Female Sexual Function (FSFI) and Mini-Mental State Examination (MMSE). Categorical variables were analyzed using simple frequency and percentages, and numerical variables by measures of position and dispersion. Data were considered with non-parametric distribution using the Kolmogorov-Smirnov test. Spearman's correlation coefficient was used to verify the correlation between the variables. p<0.05 was adopted in all tests. Participated in this study 132 elderly women (69.47 ± 6.80 years old), widows (45.45%), with incomplete primary education (37.88), BMI of 26.60 ± 4.60 kg/m², which attended the gynecologist (87.12%), on average, 0.96 ± 0.48 times a year and were sexually dissatisfied. The FGSIS score was 25.42 ± 2.95. It was observed that elderly women with a higher monthly frequency and whose last sexual activity was more recent had better genital self-image. This may be related to a positive experience of their sexuality and a greater sense of attractiveness for their partner.